Analisis Ketahanan Air Di Kota Ternate Provinsi Maluku Utara - Prieta Firdayani Mulyono; Haryono Putro (Fakultas Teknik, Universitas Brawijaya, 2019)
The biggest problem in Ternate City is availability of water and potential for natural disasters, because it is in the fire ring and climate in there is influenced by the tropical and seasonal climate. The purpose of this study is determine the water resistance in Ternate City for 20 th years until 2039. Water requirements are calculated by exponential method projections, the data based on population, industry, livestock and the area of agricultural land. Water availability debit data is based on water resources infrastructure data that has been available in there. Based on the results of the analysis, known that the total requirement of Ternate City in 2039 is 1.427 m3/ sec, total potential of mainstay discharge in 2039 is 43.139 m3/sec and total potention of dependable flow is 3 0.700 m /sec, so it can be concluded that the water demand in there is still not fulfilled to its full potential but has a great potential for reliable debits. So that, infrastructure development planning is needed in the form of as many as 98 pieces of reservoirs with a total reservoir of 5.67 million m3/sec spread across the largest watershed locations in several areas in Ternate City